Otologic Findings Based on no Complaints in a Pediatric Examination - Demir, Emine; Topal, Sevgi; Atsal, Gorkem; Erdil, Mehmet; Coskun, Zerrin Ozergin; Dursun, Engin (International Archives of Otorhinolaryngology, 2019)
Introduction the otological evaluation is highly significant in those branches of medicine in which the general evaluation of the patient is conducted by general practitioners and pediatricians.Objectives To investigate the otologic findings and their incidences in the sample, which consisted of patients who presented to the pediatric outpatient clinic with non-otologic complaints.Methods Patients, aged between 2 and 16 years, who had neither otorhinolaryngological complaints nor history of surgery by the otolaryngology (ear, nose and throat, ENT) department were included in the present study. The findings detected in the external auditory system and in the tympanic membranes as well as the otorhinolaryngologists' otologic examination findings of the referred patients were recorded from the files of each patient along with the applied medical and surgical treatments, and diagnostic investigations.Results Of a total of 973 patients evaluated, 129 (13.2%) were referred to the ENT outpatient clinic due to any otologic pathology. In the otorhinolaryngological examinations, false positivity was detected in 12 (1.2%) patients, and pathological findings were detected in 117 (12%) patients who received the following diagnoses: 68 (6.9%) had otitis media with effusion(OME); 37 (3.8%) had cerumen impactions; 8 (0.8%) had acute otitis media (AOM); 2 (0.2%) had ticks in the external auditory canal; 2 (0.2%) had a retraction pocket in tympanic membrane; 1 (0.1%) had unilateral central dry perforation of the tympanic membrane; and 1(0.1%) had congenital cholesteatoma.Conclusion Any complications and sequelae that may develop due to any pathologies and predominantly infections can be prevented by an early diagnosis, which can be made by means of a simple examination, performed merely with an otoscope. Pediatricians and general practitioners should be in close contact with otorhinolaryngologists regarding the pathologies they identify.
Keywords: otoscopy; pediatrics; otologic